Super-hydrophobic polyimide-based anticorrosive antifouling self-cleaning coating and preparation method thereof
By combining the modified graphene oxide and polyamic acid and coating the modified SiO2 composite top slurry on the surface, the problem that the existing superhydrophobic coating is difficult to have both anti-corrosion and anti-fouling self-cleaning function is solved, and the coating is realized The good mechanical properties of the layer and long-term anti-corrosion and anti-fouling effect.
Patent Information
- Application Number
- CN202411674652.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing superhydrophobic coatings are difficult to have both anti-corrosion and anti-fouling self-cleaning function and lack of mechanical performance.
Graphene oxide is modified by using modification reagents such as POSS, silane coupling agent, chain alkyl amine and chain alkyl isocyanate, combined with polyamic acid solution for composite treatment, and coated on the composite bottom surface with modification. A composite top slurry of SiO2 and binder was prepared to prepare a superhydrophobic polyimide-based anti-corrosion and anti-fouling self-cleaning coating.
It achieves good mechanical properties, self-cleaning properties and long-term anti-corrosion properties of the coating, and has excellent corrosion resistance and efficient anti-fouling effect.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of self-cleaning coating development, and relates to a super-hydrophobic polyimide-based anti-corrosion and anti-fouling self-cleaning coating and a preparation method thereof. Background Art
[0002] Superhydrophobic coatings have great application prospects in self-cleaning, anti-icing, drag reduction, anti-fouling and anti-corrosion properties. The development of micro-nanoscale material technology provides theoretical guidance for the construction of superhydrophobic coatings, and the development of modern process technology has created powerful conditions for the large-scale preparation of superhydrophobic coatings. Compared with TiO2, ZnO, carbon nanotubes and MOF-based superhydrophobic coatings, the design and synthesis of SiO2 multifunctional superhydrophobic coatings are more universal and economical. Tao et al. prepared a double-cross-linked supramolecular silicone polymer / SiO2 composite superhydrophobic coating, and the obtained coating can spontaneously and repeatedly self-repair through surface reorganization at room temperature. In addition, even after repeated mechanical or chemical damage, including sandpaper wear, solvent immersion, dripping and ultraviolet aging, the coating surface can still maintain superhydrophobicity.
[0003] At present, the resin matrix used for organic coatings has obvious defects, such as epoxy is prone to micropores and brittle fracture during curing, polyurethane has limited corrosion resistance, and polyacrylic acid has poor aging resistance, which limits the performance and practical application of organic coatings. In addition, traditional anti-corrosion coatings are difficult to meet the engineering applications under harsh conditions of ocean, acid and alkali. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a super-hydrophobic polyimide-based anti-corrosion, anti-fouling and self-cleaning coating and a preparation method thereof, thereby solving the technical problems in the prior art that the super-hydrophobic coating is difficult to simultaneously have an integrated coating with anti-corrosion, anti-fouling and self-cleaning functions and has insufficient mechanical properties.
[0005] The present invention is achieved through the following technical solutions: A method for preparing a super-hydrophobic polyimide-based anti-corrosion, anti-fouling and self-cleaning coating comprises the following steps: S1: adding a modifying agent and graphene oxide to an organic solvent A, dispersing by ultrasonication, and reacting by reflux to obtain a modified GO; the modifying agent is at least one of POSS, a silane coupling agent, a chain alkylamine, and a chain alkyl isocyanate; S2: under nitrogen protection, adding dianhydride monomers in batches to a mixed solution of diamine monomers and organic solvent B, and after reaction, obtaining a polyamic acid solution, adding the polyamic acid solution to the modified GO, and ultrasonically dispersing to obtain a composite bottom layer slurry; coating the composite bottom layer slurry on the surface of the substrate, drying, and performing thermal imidization treatment to obtain a composite bottom layer; S3: coating the surface of the composite bottom layer with a composite top layer slurry comprising alkane siloxane or perfluorosiloxane-modified SiO2 and a binder, and after drying, obtaining the super hydrophobic polyimide-based anti-corrosion, anti-fouling and self-cleaning coating.
[0006] Preferably, in step S1, the polyamic acid is POSS cross-linked polyamic acid.
[0007] Preferably, in step S1, the POSS is one of monoamino oligomeric silsesquioxane, bisamino oligomeric silsesquioxane and octaamino oligomeric silsesquioxane.
[0008] Preferably, in step S1, the number of carbon atoms in the chain alkyl group of the chain alkylamine and the chain alkyl isocyanate is 7-18.
[0009] Preferably, in step S1, the graphene oxide accounts for 2.5% to 6.5% of the mass of the modifying reagent.
[0010] Preferably, in step S2, the dianhydride monomer is a fluorine-containing dianhydride monomer and / or the diamine monomer is a fluorine-containing diamine monomer.
[0011] Preferably, in step S2, the modified GO accounts for 0.01% to 1.50% of the mass of the polyamic acid solution.
[0012] Preferably, in step S3, in the composite top layer slurry comprising alkane siloxane or perfluorosiloxane modified SiO2 and a binder, the alkane siloxane or perfluorosiloxane modified SiO2 accounts for 0.01% to 1.50% of the mass of the binder.
[0013] Preferably, in the step S3, before coating the composite top layer slurry, a PU intermediate layer is coated on the surface of the composite bottom layer, and then the composite top layer slurry is coated.
[0014] A super hydrophobic polyimide-based anti-corrosion and anti-fouling self-cleaning coating is prepared by the above method; the impedance value of the composite coating is (1.32~3.29)×10 11 Ω⋅cm 2 The contact angle of the composite coating is 152°~159°, and the low-frequency impedance value is 7.04 × 10 10 Ω⋅cm 2 .
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a method for preparing a super-hydrophobic polyimide-based anticorrosion and antifouling self-cleaning coating. In the preparation process, firstly, graphene oxide is modified by using at least one of POSS, a silane coupling agent, a chain alkylamine and a chain alkyl isocyanate, and the POSS, the silane coupling agent, the chain alkylamine and the chain alkyl isocyanate are anchored on the surface of GO by chemical bonding, so that the dispersibility of GO in the system is effectively improved, and then the modified GO is used as a part of a filler, a polyamic acid solution is added thereto, and a composite bottom layer is prepared by coating after mixing. The addition of modified GO improves defects such as micropores and cracks generated in the coating during the thermal curing process, and greatly enhances the corrosion resistance of the coating. The excellent corrosion resistance of the coating is attributed to the barrier shielding property of the polyimide resin matrix and the reinforcing effect of the functional filler; in addition, a composite top layer slurry comprising chain alkane siloxane or perfluorosiloxane modified SiO2 and a binder is coated on the surface of the composite bottom layer, which fully improves the hydrophobicity and mechanical properties of the substrate. Therefore, the coating prepared by the method of the present invention has good mechanical properties, self-cleaning properties and long-term corrosion resistance.
[0016] Furthermore, in step S1, the polyamic acid is a POSS cross-linked polyamic acid. After the polyamic acid is cross-linked and modified using a POSS reagent, it is used as a base coating to form a "star-shaped" cross-linked polyimide, which effectively enhances the shielding performance of the coating and improves the anti-corrosion effect.
[0017] Furthermore, in step S1, the number of carbon atoms in the chain alkyl group of the chain alkylamine and the chain alkyl isocyanate is 7 to 18, which allows the modification reagent to be covalently grafted to the GO surface, which on the one hand enhances the degree of GO exfoliation, and on the other hand gives the modified GO hydrophobic properties to enhance the barrier shielding effect against corrosive media.
[0018] Furthermore, in step S1, the graphene oxide accounts for 2.5% to 6.5% of the mass of the modifying agent, so that the modified graphene oxide is fully wrapped by the modifying agent, thereby effectively improving the dispersibility of the graphene oxide.
[0019] Furthermore, in step S2, the dianhydride monomer is a fluorine-containing dianhydride monomer and / or the diamine monomer is a fluorine-containing diamine monomer, which effectively enhances the hydrophobicity of the surface layer and improves the anti-corrosion effect.
[0020] Furthermore, in step S2, the modified GO accounts for 0.01% to 1.50% of the mass of the polyamic acid solution, so that the modified GO can be fully dispersed in the polyimide matrix as a filler to exert the maximum anti-corrosion performance.
[0021] Furthermore, in step S3, in the composite top layer slurry comprising alkane siloxane or perfluorosiloxane modified SiO2 and a binder, alkane siloxane or perfluorosiloxane modified SiO2 accounts for 0.01% to 1.50% of the mass of the binder. During the process, a portion of the binder is dissolved, and a portion of the binder is in a microsphere state. The alkane siloxane or perfluorosiloxane modified SiO2 adheres to the surface of the microsphere-shaped binder. During the coating and curing process, the dissolved binder bonds the modified SiO2 microspheres together to form a stacked micro-nano structure, thereby creating a super-hydrophobic surface.
[0022] Furthermore, in step S3, before coating the composite top layer slurry, a PU intermediate layer is coated on the surface of the composite bottom layer, and then the composite top layer slurry is coated. The addition of the intermediate PU layer effectively improves the bonding strength between the bottom layer coating and the top hydrophobic layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 The infrared spectrum of the NH2-POSS end-capped or suspended cross-linked fluorinated polyimide composite coating of Comparative Example 1; Figure 2 This is the infrared spectrum of the "star-shaped" cross-linked fluorinated polyimide composite coating of comparative example 2 8NH2-POSS; Figure 3 Thermogravimetric curve of the coating of Example 3; Figure 4 This is the corrosion performance test of the coating of Example 3, wherein the left figure is the Nyquist curve and the right figure is the Bode curve; Figure 5 This is the corrosion performance test of the coating of Example 4, where the left figure is the Nyquist curve and the right figure is the Bode curve; Figure 6 This is a corrosion performance test of the composite coating of Comparative Example 1, wherein the left figure is a Nyquist curve and the right figure is a Bode curve; Figure 7 This is a corrosion performance test of the composite coating of Comparative Example 2, wherein the left figure is a Nyquist curve and the right figure is a Bode curve; Figure 8The microscopic morphology and contact angle of the double-layer super-hydrophobic coating of Example 12, wherein (a) and (b) are the surface morphologies of the super-hydrophobic coating; (c) is the cross-sectional morphology of the composite coating; (d) is a diagram of the contact angle and sliding contact angle of the super-hydrophobic surface, wherein CA is the static contact angle and SA is the rolling contact angle; Fig. 9 The microscopic morphology and contact angle of the double-layer super-hydrophobic coating of Example 13, (a) is the surface morphology of the super-hydrophobic coating; (b) is the cross-sectional morphology of the composite coating; (c) is the super-hydrophobic surface contact angle and sliding contact angle diagram, in Figure (c), CA is the static contact angle, and SA is the rolling contact angle. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0026] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0027] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0028] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0029] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0030] The present invention provides a method for preparing a super-hydrophobic polyimide-based anti-corrosion, anti-fouling and self-cleaning coating, comprising the following steps: S1: adding a modifying agent and graphene oxide to an organic solvent A, dispersing by ultrasonication, and then refluxing to obtain a modified GO; the modifying agent is at least one of POSS, a silane coupling agent, a chain alkylamine, and a chain alkyl isocyanate; The POSS is one of monoamino oligomeric silsesquioxane, bisamino oligomeric silsesquioxane and octaamino oligomeric silsesquioxane. That is, the POSS used to modify GO and the POSS used to crosslink and modify polyamic acid are both one of monoamino oligomeric silsesquioxane (NH2-POSS), bisamino oligomeric silsesquioxane (2NH2-POSS) and octaamino oligomeric silsesquioxane (8NH2-POSS).
[0031] The silane coupling agent is 3-aminopropylmethyltrimethoxysilane, 3-aminopropylmethyltriethoxysilane, N-2-aminoethyl-3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-aminoethyl-3-aminopropyltriethoxysilane; In addition, in a more preferred embodiment, the number of carbon atoms in the chain alkyl group of the chain alkylamine and the chain alkyl isocyanate is 7 to 18.
[0032] The graphene oxide accounts for 2.5% to 6.5% of the mass of the modification reagent, and more preferably 1% to 3.0%.
[0033] Taking tetradecyl isocyanate as an example, the process of modifying GO with chain alkylamine or chain alkyl isocyanate is as follows: 200 mg of graphene oxide was added to 100 mL of DMF dehydrated with molecular sieves, and after ultrasonic treatment for 1 hour, 14 g of tetradecyl isocyanate was added, and ultrasonic treatment was continued for 1 hour, and then 4 to 6 drops of catalyst dibutyltin dilaurate (DBTDL) were added, and then kept at 50°C for 48 hours. The above solution was washed with 3 volumes of acetone, centrifuged at 4000 rpm, and the operation was repeated 5 times. The product was placed in a vacuum drying oven and dried to obtain chain alkyl isocyanate-modified GO.
[0034] In the above-mentioned modification process of GO, the modification reagent is grafted onto the surface of graphene oxide in a covalent bond manner.
[0035] The organic solvent A is at least one of N,N-dimethylacetamide DMAc, N,N-dimethylformamide DMF, dimethyl sulfoxide DMSO and N-methylpyrrolidone NMP.
[0036] In the preparation of graphene oxide in the present invention, natural flake graphite is used as a raw material, and graphene oxide is prepared by an improved Hummer method. The obtained graphene oxide is dialyzed in a deionized water solution for about one week, and impurity ions are removed and centrifuged before freeze-drying to obtain graphene oxide. S2: under nitrogen protection, adding dianhydride monomers in batches to a mixed solution of diamine monomers and organic solvent B, wherein the molar ratio of dianhydride monomers to diamine monomers is 1:1, and after reaction, obtaining a polyamic acid solution, adding the polyamic acid solution to the modified GO, and ultrasonically dispersing for 10 to 60 minutes, preferably 10 to 30 minutes, to obtain a composite bottom layer slurry, wherein the solid content of the composite bottom layer slurry is 8wt% to 20wt%; coating the composite bottom layer slurry on the surface of the substrate, drying, and then performing thermal imidization treatment to obtain a composite bottom layer; Among them, the dianhydride monomer is 4,4'-oxydiphthalic anhydride, 4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride), pyromellitic anhydride, biphenyltetracarboxylic anhydride, triphenyl ether carboxylic anhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]hexafluoropropane dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)phthalic anhydride, 1,3- One or more of bis(3,4-dicarboxyphenoxy)phthalic anhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl sulfone dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)benzophenone dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride, and 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl ether dianhydride.
[0037] The diamine monomers are 4,4'-diaminodiphenyl ether, 4,4'-(1,4-phenylenedioxy)dianiline, 4,4'-diaminodiphenylmethane, 1,4-phenylenediamine, N-phenyl-1,4-phenylenediamine, 2,2'-bis[4-(4-aminophenoxyphenyl)]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis[4-(3-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis[4-(2-trifluoromethyl-4-aminophenoxy)phenyl]propane, 2,2-[4-(2- 4,4'-bis(2-trifluoromethyl-4-aminophenoxy)benzophenone, 4,4'-bis(2-trifluoromethyl-4-aminophenoxy)diphenyl sulfone, 4,4'-bis(2-trifluoromethyl-4-aminophenoxy)diphenyl sulfide, 4,4'-bis(2-trifluoromethyl-4-aminophenoxy)biphenyl, 1,3-bis(2-trifluoromethyl-4-aminophenoxy)benzene, 1,4-bis(2-trifluoromethyl-4-aminophenoxy)benzene, 1,3-bis[3'-trifluoromethyl-4'(4''-aminophenoxy)phenyl]benzene, 1,3-bis(4-amino-2-trifluoromethylphenoxy)benzene, 4,4''-bis(aminophenoxy)-3,3'-trifluoromethylterphenyl, 4 , one or more of 4-bis[3'-trifluoromethyl-4'(4''-aminophenoxy)phenyl]biphenyl.
[0038] In a preferred embodiment, the dianhydride monomer is a fluorine-containing dianhydride monomer and / or the diamine monomer is a fluorine-containing diamine monomer.
[0039] In step S2, the modified GO accounts for 0.01% to 1.50% of the mass of the polyamic acid solution, preferably 0.02% to 1.0%, and more preferably 0.3% to 0.9%.
[0040] The organic solvent B is at least one of N,N-dimethylacetamide DMAc, N,N-dimethylformamide DMF, N-methylpyrrolidone NMP, dimethyl sulfoxide DMSO and diacetone alcohol.
[0041] In a preferred embodiment, the polyamic acid is a polyamic acid cross-linked with POSS, that is, under nitrogen protection, the dianhydride monomer is added in batches to a mixed solution of diamine monomer and organic solvent B, and a POSS reagent is added. After the reaction, a polyamic acid solution cross-linked and modified with POSS is obtained; before the polyamic acid solution is added to the modified GO, the modified GO is first dispersed in N, N-dimethylacetamide DMAc, N, N-dimethylformamide DMF, dimethyl sulfoxide DMSO or N-methylpyrrolidone NMP, and pre-dispersed, and then the polyamic acid is added to the fully dispersed functionalized GO solution, and further ultrasonically dispersed. Compared with directly adding functionalized graphene oxide to polyamic acid, the pre-dispersion method can avoid the functionalized graphene oxide from being wrapped by polymers to cause a large amount of agglomeration or uneven dispersion. The above-mentioned experimental sequence is helpful for dispersion, mainly utilizing the density difference caused by the gravity sedimentation of the latter to promote dispersion. The uniform dispersion and stability of modified graphene oxide in the coating can effectively promote its excellent barrier effect as a two-dimensional nanofunctional filler. The polyimide-based composite slurry obtained by the two-step method can be stably stored at room temperature for about 2 weeks without obvious precipitation.
[0042] The added POSS agent accounts for 1% to 10% of the mass of the polyamic acid, preferably 3% to 5%.
[0043] Before coating the composite bottom layer slurry, the surface of the substrate is degreased, roughened and ultrasonically cleaned to effectively increase the adhesion of the material.
[0044] The composite bottom layer slurry is coated on the surface of the substrate, dried, and then subjected to thermal imidization treatment to obtain the composite bottom layer. Specifically, the sprayed sample is placed at room temperature for 1 to 2 hours to achieve surface drying, and then subjected to a programmed thermal imidization treatment. The thermal imidization process includes volatilizing a large amount of solvent at 80°C to 135°C, preferably curing at 135°C for 3 hours, and then completing imidization at 200 to 300°C, performing preliminary imidization at 200°C (2 hours), and more thorough imidization is completed at 240 to 300°C due to different imide systems, and curing for about 1 hour.
[0045] The coating can be sprayed or brushed. In the spraying process, the composite base layer slurry is evenly dispersed by ultrasound and sprayed on the metal substrate or part surface with a spray gun under 0.2 MPa oil-free compressed air or compressed nitrogen. The number of spraying is 10 to 30 times, preferably 15 to 20 times. After drying, the composite base layer with a thickness of 1 to 100 μm, preferably 35 to 45 μm, is obtained. The thickness is measured using a MINITEST 1100 coating thickness gauge.
[0046] The metal substrate is an electro-galvanized steel plate, a 304 stainless steel plate, a cold-rolled plate, a galvanized steel plate, an aluminum alloy plate or a metal part of any shape.
[0047] S3: coating the surface of the composite bottom layer with a composite top layer slurry comprising alkane siloxane or perfluorosiloxane-modified SiO2 and a binder, and after drying, obtaining the super hydrophobic polyimide-based anti-corrosion, anti-fouling and self-cleaning coating.
[0048] The above-mentioned paraffin siloxane is dodecyl siloxane or hexadecyl siloxane; The perfluorosiloxane is perfluorodecyltrimethoxysilane, perfluorodecyltriethoxysilane, perfluorooctyltrimethoxysilane, or perfluorooctyltriethoxysilane.
[0049] In the modification process of SiO2, the modification reagent reacts and combines with the nano-SiO2 in a covalent bond manner through dehydration condensation.
[0050] The particle size of the SiO2 modified by the alkane siloxane or perfluorosiloxane is 10-40 nm.
[0051] In the above process, in the composite top layer slurry comprising alkane siloxane or perfluorosiloxane modified SiO2 and a binder, the alkane siloxane or perfluorosiloxane modified SiO2 accounts for 0.01% to 1.50% of the mass of the binder.
[0052] The adhesive includes at least one of polyurethane, polyolefin, epoxy resin and polyacrylic acid.
[0053] The above-mentioned composite coating is used as the base layer to prepare a super-hydrophobic coating on its surface, and an adhesive is used to prepare a super-hydrophobic layer by compounding and modifying low surface energy nano-SiO2. On the one hand, SiO2 particles are bonded to create a micro-nano rough surface, and the adhesive is also firmly bonded to the surface of the composite coating. In addition, polyurethane or epoxy adhesive can also be used as an intermediate transition layer between the composite coating and the super-hydrophobic coating, which plays two roles: one is to make different levels firmly bonded, and the other is to embed a super-hydrophobic layer in the intermediate transition layer to increase the mechanical durability of the super-hydrophobic layer.
[0054] In the step S3, before coating the composite top layer slurry, a PU intermediate layer is coated on the surface of the composite bottom layer, and then the composite top layer slurry is coated. Here, PU is polyurethane.
[0055] The present invention also discloses a super-hydrophobic polyimide-based anti-corrosion and anti-fouling self-cleaning coating, which is prepared by the above method; the impedance value of the composite coating is (1.32~3.29)×10 11 Ω⋅cm 2 The contact angle of the composite coating is 152°~159°, and after 50 days of neutral salt spray test, it still has good anti-corrosion performance and the low-frequency impedance value is as high as 7.04 × 10 10 Ω⋅cm2 , the double-layer or sandwich super-hydrophobic coating still has super-hydrophobic properties after 100 sandpaper abrasions and 80 tape glass mechanical tests.
[0056] The invention discloses a method for preparing a super-hydrophobic polyimide-based anti-corrosion, anti-fouling and self-cleaning coating. The preparation method uses polyimide as a main film-forming substance of the coating. The polyimide may be a certain fluorine-containing or non-fluorine-containing molecular structure, or may be a blend of two or more, or may even be a polyimide cross-linked in a "star-shaped" manner using octaamino oligomeric silsesquioxane (8NH2-POSS). A functionalized graphene oxide two-dimensional filler is stably dispersed in a coating resin matrix to avoid the common problem that graphene or graphene oxide cannot be evenly and stably dispersed when directly used, and the functionalized two-dimensional filler is added to improve defects such as micropores and cracks generated in the coating during thermal curing, while greatly enhancing the anti-corrosion performance of the coating. The excellent corrosion resistance of the coating is attributed to the barrier shielding property of the polyimide resin matrix and the reinforcing effect of the functional filler. In addition, a super-hydrophobic coating is prepared based on the composite coating, and a slurry of long-chain alkane siloxane or perfluorosiloxane-modified nano-SiO2 and a composite binder is sprayed on the surface of the composite coating to prepare a double-layer or "sandwich" super-hydrophobic coating to form a multi-layer isolation barrier. This functional coating combines the corrosion resistance of the composite coating with the significant anti-fouling and self-cleaning properties of the super-hydrophobic coating, so that the prepared multi-layer organic composite super-hydrophobic coating has excellent corrosion resistance, anti-fouling and self-cleaning properties.
[0057] The present invention uses polyimide (non-fluorine-containing or fluorine-containing) or POSS-crosslinked polyimide as the base resin of the composite coating to prepare a polyimide-based composite anticorrosive coating that is intrinsically hydrophobic, has controllable thickness and is resistant to high temperatures. Fluorinated polyimide has very stable aromatic heterocyclic structural units and hydrophobic trifluoromethyl and other functional groups in the chain segments. POSS with hydrophobic and interfacial compatibility functions is further introduced into the fluorinated polyimide molecule by POSS "end-capping" or "star-shaped" crosslinking. This POSS-hybridized polyimide has intrinsic hydrophobicity, mechanical properties and excellent anticorrosive properties as a composite coating base resin. Its glass transition temperature is generally above 200°C, and its initial decomposition temperature is above 500°C, with high heat resistance. Electrochemical tests have shown that the impedance value of the fluorinated polyimide-based composite coating is as high as 1.58×10 11 Ω⋅cm 2 The impedance value of the non-fluorinated polyimide-based composite coating reached 1.32×10 11 Ω⋅cm 2 The impedance value of the POSS cross-linked fluorinated polyimide composite coating reached 3.29×10 11 Ω⋅cm 2 , which indicates that the polyimide-based composite coating has excellent anti-corrosion performance.
[0058] The fluorinated polyimide, non-fluorinated polyimide and POSS cross-linked polyimide-based composite anticorrosive coating prepared by the present invention has high heat resistance, good mechanical properties and excellent intrinsic hydrophobicity, and the coating thickness can be controlled by changing the number of spraying times and adjusting the spraying flow rate.
[0059] A kind of polyimide or POSS cross-linked polyimide-based composite anticorrosion coating prepared by the present invention contains the hydrophobic crown energy group of POSS and trifluoromethyl etc. due to the main chain of polymer molecules, and coating has lower moisture absorption rate, showing excellent corrosion resistance. A kind of polyimide-based composite super-hydrophobic coating prepared by the present invention, with composite coating as base layer, then SiO2 super-hydrophobic slurry is sprayed on its surface to prepare multi-layer composite super-hydrophobic coating. The polyimide-based composite super-hydrophobic coating prepared by the present invention, combines the excellent barrier shielding performance of composite coating and the remarkable self-cleaning and antifouling performance of super-hydrophobic coating, gives multi-layer super-hydrophobic coating self-cleaning antifouling and anticorrosion comprehensive performance.
[0060] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0061] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0062] Example 1 Pre-oxidation of natural flake graphene: Add 30 mL of concentrated sulfuric acid to a 250 ml three-necked flask equipped with mechanical stirring in a 25 °C water bath, and add 5 g of natural flake graphene, 3 g of potassium persulfate, and 8 g of phosphorus pentoxide under stirring. Slowly increase the temperature to 60 °C for oxidation for 3 h, then cool to 25 °C and continue oxidation for 5 h. At the end of the experiment, filter and wash until the filtrate is neutral. The product is vacuum dried at 50 °C for 24 h before use.
[0063] Preparation of graphene oxide: In a 25 °C water bath, add 360 mL of concentrated sulfuric acid and 40 mL of phosphoric acid to a 500 mL three-necked flask equipped with a mechanical stirrer, add 3 g of pre-oxidized graphene under rapid stirring, mix well, add 18 g of potassium permanganate powder within 2 h, then heat to 50 °C and maintain this temperature for 12 h before cooling to 25 °C. Pour the reaction liquid into 400 mL of ice water under stirring, add 30% hydrogen peroxide solution dropwise to make the system bright yellow and no bubbles are generated, add an equal volume of 10% dilute hydrochloric acid solution, and remove SO4 by dialysis. 2- The impurity ions are removed and then concentrated by centrifugation, and the concentrated solution is freeze-dried to obtain graphene oxide.
[0064] Example 2 Preparation of functionalized graphene oxide: (1) Mono-NH2-POSS functionalized graphene oxide: 350 mg of graphene oxide, 5.0 g of NH2-POSS, 100 mg of dicyclohexylcarbodiimide and 50 mL of tetrahydrofuran were accurately weighed and dissolved in a 250 mL single-necked flask and ultrasonicated for 30 min. The above-mentioned dispersed solution was then refluxed for 48 h, and then the solvent was removed by rotary evaporation. The product was heat treated at 120 °C for 12 h to obtain the product.
[0065] The above product was dissolved in 50 mL of tetrahydrofuran and precipitated in 500 mL of methanol. The experiment was repeated three times to remove unreacted NH2-POSS. Then, the final product was filtered using a 0.22 μm organic filter membrane, dried in a vacuum at 80 °C, and stored for later use.
[0066] (2) γ-Methacryloxypropyltrimethoxysilane (KH570) functionalized graphene oxide: 500 mg KH570 and 50 g anhydrous ethanol were added into a 250 mL single-necked flask and ultrasonicated for 30 min. The dispersed solution was then refluxed for 24 h. The product was then washed alternately with deionized water and anhydrous ethanol three times and dried at 80 °C for 24 h to obtain KH570-modified graphene oxide.
[0067] Example 3 Graphene oxide was prepared by the same improved Hummer method as in Example 1. Functionalized graphene oxide was prepared by the same method as in Example 2 (1). Under nitrogen protection, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane and 4,4'-(hexafluoroisopropylene)diphthalic anhydride in a molar ratio of 1:1 were reacted at room temperature for 6 h and 80 °C for 4 h to synthesize fluorinated polyamide acid. A fluorinated polyamide acid mixed solution with a mass fraction of 0.3 wt.% of functionalized graphene oxide (Example 2 (1)) was prepared; the prepared mixed solution was sprayed on a metal substrate by spraying, and a fluorinated polyimide-based composite coating was obtained by room temperature pre-curing and high temperature program temperature control of 135, 205 and 280 °C for curing time of 3, 1 and 1 h, respectively. The coating thickness was 42 μm.
[0068] Example 4 Graphene oxide was prepared by the same improved Hummer method as in Example 1. Functionalized graphene oxide was prepared by the same method as in Example 2 (1). Under nitrogen protection, polyamic acid was synthesized by reacting at room temperature for 4 h and at 70 °C for 2 h, respectively, with a molar ratio of 1:1 of 4,4'-diaminodiphenyl ether and 4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride). A polyamic acid mixed solution of functionalized graphene oxide (Example 2 (1)) with a mass fraction of 0.3 wt.% was prepared; the prepared mixed solution was sprayed on a metal substrate by spraying, and a polyimide-based composite coating was obtained by room temperature pre-curing and high temperature program temperature control of 135, 210 and 280 °C for curing time of 3, 1 and 1 h, respectively. The coating thickness was 44 μm.
[0069] Example 5 Graphene oxide was prepared by the same method as in Example 1, and functionalized graphene oxide was prepared by the same method as in Example 2 (2). Fluorinated polyamic acid was synthesized by the same method as in Example 3. A fluorinated polyamic acid mixed solution of 0.3 wt % of functionalized graphene oxide (Example 2 (2)) was prepared; the prepared mixed solution was sprayed on a metal substrate, and a fluorinated polyimide-based composite coating was obtained by pre-curing at room temperature and thermal imidization at high temperature with a curing time of 3, 1 and 1 h, respectively, at 135, 205 and 280 ° C. The coating thickness was 44 μm.
[0070] Example 6 Graphene oxide was prepared by the same method as in Example 1, and functionalized graphene oxide was prepared by the same method as in Example 2 (2). Polyamic acid was synthesized by the same method as in Example 4. A polyamic acid mixed solution of functionalized graphene oxide (Example 2 (2)) with a mass fraction of 0.3 wt% was prepared; the prepared mixed solution was sprayed on a metal substrate, and a polyimide-based composite coating was obtained by pre-curing at room temperature and thermal imidization at high temperature program temperature control of 135, 210 and 280°C for curing times of 3, 1 and 1 h, respectively. The coating thickness was 45 μm.
[0071] Example 7 Graphene oxide was prepared by the same improved Hummer method as in Example 1; functionalized graphene oxide was prepared by the same method as in Example 2 (1). Fluorinated polyamic acid was synthesized by the same method as in Example 3. A fluorinated polyamic acid mixed solution of 0.3 wt % of functionalized graphene oxide (Example 2 (1)) was prepared; the prepared mixed solution was sprayed on a metal substrate, and a fluorinated polyimide-based composite coating was obtained by pre-curing at room temperature and thermal imidization at high temperature program temperature control of 135, 205 and 280 ° C for curing times of 3, 1 and 1 h, respectively. The coating thickness was 43 μm.
[0072] Example 8 Graphene oxide was prepared by the same improved Hummer method as in Example 1; functionalized graphene oxide was prepared by the same method as in Example 2 (1). Polyamic acid was synthesized by the same method as in Example 4. A polyamic acid mixed solution of functionalized graphene oxide (Example 2 (1)) with a mass fraction of 0.5 wt% was prepared; the prepared mixed solution was sprayed on a metal substrate, and a polyimide-based composite coating was obtained by pre-curing at room temperature and thermal imidization at high temperature program temperature control of 135, 210 and 280°C for curing times of 3, 1 and 1 h, respectively. The coating thickness was 45 μm.
[0073] Example 9 Graphene oxide was prepared by the same improved Hummer method as in Example 1; functionalized graphene oxide was prepared by the same method as in Example 2 (2). Fluorinated polyamic acid was synthesized by the same method as in Example 3. Functionalized graphene oxide (Example 2 (2)) with a mass fraction of 0.5 wt% was added to the fluorinated polyamic acid slurry; the prepared mixed solution was sprayed on a metal substrate, and subjected to thermal imidization at 135, 280 and 300 °C for curing times of 2, 1 and 0.5 h, respectively, to obtain a fluorinated polyimide composite anti-corrosion coating with a coating thickness of 42 μm.
[0074] Example 10 Graphene oxide was prepared by the same improved Hummer method as in Example 1; functionalized graphene oxide was prepared by the same method as in Example 2 (2). Polyamic acid was synthesized by the same method as in Example 4. Functionalized graphene oxide (Example 2 (2)) with a mass fraction of 0.5 wt% was added to the polyamic acid slurry; the prepared mixed solution was sprayed on a metal substrate, and subjected to thermal imidization at 135, 260 and 280°C for curing times of 2, 1 and 0.5 h, respectively, to obtain a polyimide composite anti-corrosion coating with a coating thickness of 43 μm.
[0075] The same synthesis method as in Example 3 was used to obtain fluorinated polyamic acid, and a mixed solution of polyamic acid with the same mass content as the composite coating was sprayed on a metal substrate. After a thermal imidization process at 135, 280 and 300 °C with curing times of 2, 1 and 0.5 h, respectively, a fluorinated polyimide coating was obtained. The coating thickness was 46 μm, which was recorded as a blank sample.
[0076] Comparative Example 1 The fluorinated polyamic acid was synthesized by the same method as in Example 3, and then 5 wt % NH2-POSS was added at room temperature and the reaction was maintained at room temperature for 10 h to further obtain POSS-terminated or side-chain suspended fluorinated polyamic acid. At the same time, the functionalized graphene oxide (Example 2 (1)) with the same mass content as in Example 3 was added to obtain a mixed slurry. The slurry was sprayed on a metal substrate at a pressure of 0.2 MPa, and subjected to a thermal imidization process at 135, 280 and 300 °C and curing times of 2, 1 and 0.5 h, respectively, to obtain a POSS-suspended or end-capped fluorinated polyimide coating with a coating thickness of 42 μm, which was recorded as the comparison sample of Example 3.
[0077] Comparative Example 2 The fluorinated polyamic acid was synthesized by the same method as in Example 3, and then 8NH2-POSS with a mass fraction of 5 wt% of the acid was added at room temperature and the reaction was maintained at room temperature for 10 h to further obtain POSS "star-shaped" cross-linked fluorinated polyamic acid. At the same time, functionalized graphene oxide (Example 2 (2)) with the same mass content as in Example 3 was added to obtain a mixed slurry. The slurry was sprayed on a metal substrate at a pressure of 0.2 MPa, and subjected to a thermal imidization process at 135, 280 and 300 °C and curing times of 2, 1 and 0.5 h, respectively, to obtain a POSS "star-shaped" cross-linked fluorinated polyimide coating with a coating thickness of 42 μm, which was recorded as the comparison sample of Example 4.
[0078] Embodiment 11 A polyamic acid mixed solution with a mass fraction of 0.5 wt % of functionalized graphene oxide (Example 2 (1)) was prepared; the prepared mixed solution was sprayed on a metal substrate, and a polyimide-based composite coating was obtained by pre-curing at room temperature and thermal imidization at high temperature with a program temperature control of 135, 210 and 280 ° C for curing times of 3, 1 and 1 h, respectively. The coating thickness was 45 μm.
[0079] Example 12 Preparation of super-hydrophobic coating: 2.5 g of SiO2 was added to a mixed solution of 500 mL of ethanol and 2.5 g of sodium methylsilanol, stirred at 500 r / min for 20 min, and then ultrasonically dispersed for 20 min. At room temperature, 0.75 mL of tetraethyl silicate (TEOS) was then added, and 5 mL of hexadecyltrimethoxysilane (HDTMS) was added dropwise after maintaining high-speed stirring for 30 min. After the addition, stirring was continued for 2 h to terminate the reaction experiment. The modified nano-SiO2 suspension was centrifuged at 8000 r / min and washed three times with anhydrous ethanol. The washed nano-SiO2 solid was vacuum dried at 60 °C for 12 h to obtain a super-hydrophobic modified nano-SiO2 powder, named HD-SiO2.
[0080] Preparation of super-hydrophobic suspension: 1.2 g of POA was dissolved in 3 g of butyl acetate, magnetically stirred at room temperature for 30 min, and 3 g of ethyl acetate solution was added. The obtained mixed solution was recorded as liquid A. At the same time, 1.5 g of anhydrous ethanol was added to a sample bottle of 1.0 g of HD-SiO2, and ultrasonicated for 30 min. The obtained semi-solid was recorded as liquid B. Then, liquid B was added dropwise to the above liquid A and stirred for 1.5 h to obtain a super-hydrophobic suspension. Then, the above suspension was transferred to a spray gun and sprayed on the surface of the composite coating prepared in Example 3 under an air pressure of 0.2 MPa. The caliber of the spray gun was 1.0 mm. During the spraying process, the distance between the spray gun and the coating was kept at 12-20 cm. The spray speed was controlled and the spray gun was slowly moved from top to bottom along an "S" shape. This ensured that the prepared super-hydrophobic coating had a uniform and compact roughness to ensure the mechanical durability and continuous water transport of the super-hydrophobic coating. The prepared upper super-hydrophobic layer was named POA / HD-SiO2, and the double-layer super-hydrophobic coating was named FPI / POSS-GO@POA / HD-SiO2. The super-hydrophobic coating was obtained by curing at room temperature for 24 h.
[0081] Example 13 Preparation of super-hydrophobic coating: 3.0 g hydrophilic nano-SiO2 (10 ~ 35 nm) was dispersed in 150 mL ethanol / water mixed solution, mechanically stirred for 20 min, and then ultrasonically dispersed for 20 min to ensure full dispersion. Subsequently, 3 g of sodium methylsilanol was added to the above dispersion under continuous mechanical stirring at 500 r / min and continued to stir for 20 min. Secondly, 3200 μL perfluoroquinoline triethoxysilane and 900 μL TEOS were added to the reaction mixture and continued to stir at room temperature for 1.5 h. At this time, the solution became a uniform milky white state. The modified nano-SiO2 suspension was centrifuged at 8000 r / min and washed three times with anhydrous ethanol. The washed modified nano-SiO2 semi-solid was vacuum dried at 60 °C for 6 h to obtain fluorinated nano-SiO2 powder, named POA / PF-SiO2.
[0082] Then 1.4 g of POA was dissolved in 5.5 g of butyl acetate and magnetically stirred at room temperature for 30 min. At this time, a nearly semi-solid slurry mixed with 1.2 g of PF-SiO2 and 2.0 g of anhydrous ethanol that had been ultrasonically pretreated was added dropwise to the above solution, and magnetic stirring was continued for 2 h and ultrasonic dispersion was performed for 30 min to obtain a super-hydrophobic suspension. Finally, the above suspension was transferred to a spray gun and sprayed on the surface of the B-FPI / POSS-4 polymer nanocomposite coating at an air pressure of 0.2 MPa. During the spraying process, the distance between the spray gun and the coating was kept at 10 to 20 cm, the spray speed was controlled, and the spray gun was slowly moved from top to bottom along the "S" shape. This ensured that the prepared super-hydrophobic coating had a uniform and compact roughness to ensure the mechanical durability and continuous water transport of the super-hydrophobic coating. The prepared double-layer super-hydrophobic layer was named FPI / POSS-GO@PF-SiO2, and the super-hydrophobic coating was obtained by curing at room temperature for 24 h.
[0083] Embodiment 14 Preparation of super-hydrophobic coating: 2.5 g of SiO2 was added to a mixed solution of 500 mL of ethanol and 2.5 g of sodium methylsilanol, stirred at 500 r / min for 20 min, and then ultrasonically dispersed for 20 min. At room temperature, 0.75 mL of tetraethyl silicate (TEOS) was then added, and 5 mL of hexadecyltrimethoxysilane (HDTMS) was added dropwise after maintaining high-speed stirring for 30 min. After the addition, stirring was continued for 2 h to terminate the reaction experiment. The modified nano-SiO2 suspension was centrifuged at 8000 r / min and washed three times with anhydrous ethanol. The washed nano-SiO2 solid was vacuum dried at 60 °C for 12 h to obtain a super-hydrophobic modified nano-SiO2 powder, named HD-SiO2.
[0084] Preparation of super-hydrophobic suspension: 1.2 g of POA was dissolved in 3 g of butyl acetate, magnetically stirred at room temperature for 30 min, and 3 g of ethyl acetate solution was added. The obtained mixed solution was recorded as liquid A. At the same time, 1.5 g of anhydrous ethanol was added to a sample bottle of 1.0 g of HD-SiO2, and ultrasonicated for 30 min. The obtained semi-solid was recorded as liquid B. Then, liquid B was added dropwise to the above liquid A and stirred for 1.5 h to obtain a super-hydrophobic suspension. Then, the above suspension was transferred to a spray gun and sprayed on the surface of the composite coating prepared in Example 4 under an air pressure of 0.2 MPa. The caliber of the spray gun was 1.0 mm. During the spraying process, the distance between the spray gun and the coating was kept at 12-20 cm. The spray speed was controlled and the spray gun was slowly moved from top to bottom along an "S" shape. This ensured that the prepared super-hydrophobic coating had a uniform and compact roughness to ensure the mechanical durability and continuous water transport of the super-hydrophobic coating. The prepared upper super-hydrophobic layer was named POA / HD-SiO2, and the double-layer super-hydrophobic coating was named PI / POSS-GO@POA / HD-SiO2. The super-hydrophobic coating was obtained by curing at room temperature for 24 h.
[0085] Embodiment 15 Preparation of super-hydrophobic coating: 3.0 g hydrophilic nano-SiO2 (10 ~ 35 nm) was dispersed in 150 mL ethanol / water mixed solution, mechanically stirred for 20 min, and then ultrasonically dispersed for 20 min to ensure full dispersion. Subsequently, 3 g of sodium methylsilanol was added to the above dispersion under continuous mechanical stirring at 500 r / min and continued to stir for 20 min. Secondly, 3200 μL perfluoroquinoline triethoxysilane and 900 μL TEOS were added to the reaction mixture and continued to stir at room temperature for 1.5 h. At this time, the solution became a uniform milky white state. The modified nano-SiO2 suspension was centrifuged at 8000 r / min and washed three times with anhydrous ethanol. The washed modified nano-SiO2 semi-solid was vacuum dried at 60 °C for 6 h to obtain fluorinated nano-SiO2 powder, named POA / PF-SiO2.
[0086] Then 1.4 g of POA is dissolved in 5.5 g of butyl acetate, magnetically stirred at room temperature for 30 min, now by 1.2 g of PF-SiO2 mixed with 2.0 g of anhydrous ethanol for ultrasonic pretreatment, the nearly semi-solid slurry is added dropwise to the above-mentioned solution, and ultrasonic dispersion is continued for 30 min after 2 h of magnetic stirring to obtain super-hydrophobic suspension. Finally, the above-mentioned suspension is transferred to a spray gun, sprayed on the composite coating surface prepared in Example 4 under 0.2 MPa air pressure, and the distance between the spray gun and the coating is kept to be 10 ~ 20 cm during the spraying process, the spray speed is controlled, and the spray gun is slowly moved from top to bottom along the "S" shape, so that the prepared super-hydrophobic coating can be ensured to have uniform and compact roughness, to ensure that the mechanical durability and continuous water delivery of the super-hydrophobic coating, the prepared double-layer super-hydrophobic layer is named PI / POSS-GO@PF-SiO2, and the super-hydrophobic coating can be obtained by curing for 24 h at room temperature.
[0087] Example 16 This embodiment discloses a method for preparing a super-hydrophobic polyimide-based anti-corrosion, anti-fouling and self-cleaning coating, comprising the following steps: Under nitrogen protection, 4,4'-oxydiphthalic anhydride is added in batches to a mixed solution of 4,4'-diaminodiphenyl ether, 4,4'-(1,4-phenylenedioxy) dianiline and N,N-dimethylacetamide DMAc, wherein the molar ratio of the dianhydride monomer to the diamine monomer is 1:1, and after reaction, a polyamic acid solution is obtained, and the polyamic acid solution is added to the monoamino oligomeric silsesquioxane-modified graphene oxide, and ultrasonically dispersed for 10 to 60 minutes, preferably 10 to 30 minutes, to obtain a composite bottom layer slurry, wherein the solid content of the composite bottom layer slurry is 8wt% to 20wt%; the composite bottom layer slurry is coated on the surface of the substrate, and after drying, a thermal imidization treatment is performed to obtain a composite bottom layer; The monoamino oligomeric silsesquioxane-modified graphene oxide accounts for 0.01% of the mass of the polyamic acid solution.
[0088] A PU middle layer is coated on the surface of the composite bottom layer. After drying, a composite top layer slurry comprising dodecylsiloxane-modified SiO2 and a binder is coated on the surface of the PU middle layer. After drying, the super-hydrophobic polyimide-based anti-corrosion, anti-fouling and self-cleaning coating is obtained.
[0089] The particle size of the dodecylsiloxane-modified SiO2 is 10 nm.
[0090] In the above process, in the composite top layer slurry comprising dodecylsiloxane-modified SiO2 and a binder, dodecylsiloxane-modified SiO2 accounts for 0.01% of the mass of the binder.
[0091] The above-mentioned adhesive is polyurethane.
[0092] Embodiment 17 This embodiment discloses a method for preparing a super-hydrophobic polyimide-based anti-corrosion, anti-fouling and self-cleaning coating, comprising the following steps: Under nitrogen protection, 4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride) is added in batches to a mixed solution of 2,2'-bis[4-(4-aminophenoxyphenyl)]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane and N,N-dimethylformamide DMF, wherein the molar ratio of the dianhydride monomer to the diamine monomer is 1:1, and after reaction, a polyamic acid solution is obtained, and the polyamic acid solution is added to the 3-aminopropylmethyltrimethoxysilane-modified graphene oxide, and ultrasonically dispersed for 10 to 60 minutes, preferably 10 to 30 minutes, to obtain a composite bottom layer slurry, wherein the solid content of the composite bottom layer slurry is 8wt% to 20wt%; the composite bottom layer slurry is coated on the surface of the substrate, and after drying, a thermal imidization treatment is performed to obtain a composite bottom layer; The modified GO accounts for 1.50% of the mass of the polyamic acid solution.
[0093] A PU middle layer is coated on the surface of the composite bottom layer. After drying, a composite top layer slurry comprising perfluorodecyltrimethoxysilane-modified SiO2 and a binder is coated on the surface of the PU middle layer. After drying, the super-hydrophobic polyimide-based anti-corrosion, anti-fouling and self-cleaning coating is obtained.
[0094] The particle size of the perfluorodecyltrimethoxysilane-modified SiO2 is 40 nm.
[0095] In the above process, in the composite top layer slurry comprising perfluorodecyltrimethoxysilane-modified SiO2 and a binder, the perfluorodecyltrimethoxysilane-modified SiO2 accounts for 1.50% of the mass of the binder.
[0096] The above-mentioned adhesive is polyurethane.
[0097] Embodiment 18 This embodiment discloses a method for preparing a super-hydrophobic polyimide-based anti-corrosion, anti-fouling and self-cleaning coating, comprising the following steps: S1: adding a modifying agent and graphene oxide to an organic solvent A, dispersing by ultrasonication, and reacting by reflux to obtain a modified GO; the modifying agent is at least one of POSS, a silane coupling agent, a chain alkylamine, and a chain alkyl isocyanate; Graphene oxide accounts for 2.5% of the mass of the modification reagent.
[0098] S2: under nitrogen protection, adding dianhydride monomers in batches to a mixed solution of diamine monomers and organic solvent B, wherein the molar ratio of dianhydride monomers to diamine monomers is 1:1, and after reaction, obtaining a polyamic acid solution, adding the polyamic acid solution to the modified GO, and ultrasonically dispersing for 10 to 60 minutes, preferably 10 to 30 minutes, to obtain a composite bottom layer slurry, wherein the solid content of the composite bottom layer slurry is 8wt% to 20wt%; coating the composite bottom layer slurry on the surface of the substrate, drying, and then performing thermal imidization treatment to obtain a composite bottom layer; The modified GO accounts for 1.0% of the mass of the polyamic acid solution.
[0099] S3: A PU middle layer is coated on the surface of the composite bottom layer. After drying, a composite top layer slurry comprising alkane siloxane or perfluorosiloxane-modified SiO2 and a binder is coated on the surface of the PU middle layer. After drying, the super hydrophobic polyimide-based anti-corrosion, anti-fouling and self-cleaning coating is obtained.
[0100] In the above process, in the composite top layer slurry comprising alkane siloxane or perfluorosiloxane modified SiO2 and a binder, the alkane siloxane or perfluorosiloxane modified SiO2 accounts for 1.0% of the mass of the binder.
[0101] The above-mentioned adhesive is polyacrylic acid.
[0102] Embodiment 19 This embodiment discloses a method for preparing a super-hydrophobic polyimide-based anti-corrosion, anti-fouling and self-cleaning coating, comprising the following steps: S1: adding a modifying agent and graphene oxide to an organic solvent A, dispersing by ultrasonication, and reacting by reflux to obtain a modified GO; the modifying agent is at least one of POSS, a silane coupling agent, a chain alkylamine, and a chain alkyl isocyanate; The above-mentioned graphene oxide accounts for 1% of the mass of the modification reagent.
[0103] S2: under nitrogen protection, adding dianhydride monomers in batches to a mixed solution of diamine monomers and organic solvent B, wherein the molar ratio of dianhydride monomers to diamine monomers is 1:1, and after reaction, obtaining a polyamic acid solution, adding the polyamic acid solution to the modified GO, and ultrasonically dispersing for 10 to 60 minutes, preferably 10 to 30 minutes, to obtain a composite bottom layer slurry, wherein the solid content of the composite bottom layer slurry is 8wt%; coating the composite bottom layer slurry on the surface of the substrate, drying, and then performing thermal imidization treatment to obtain a composite bottom layer; In step S2, the modified GO accounts for 0.3% of the mass of the polyamic acid solution.
[0104] S3: A PU middle layer is coated on the surface of the composite bottom layer. After drying, a composite top layer slurry comprising alkane siloxane or perfluorosiloxane-modified SiO2 and a binder is coated on the surface of the PU middle layer. After drying, the super hydrophobic polyimide-based anti-corrosion, anti-fouling and self-cleaning coating is obtained.
[0105] The particle size of the SiO2 modified by the alkane siloxane or perfluorosiloxane is 20 nm.
[0106] In the above process, in the composite top layer slurry comprising alkane siloxane or perfluorosiloxane modified SiO2 and a binder, the alkane siloxane or perfluorosiloxane modified SiO2 accounts for 1.2% of the mass of the binder.
[0107] The above-mentioned adhesive is epoxy resin.
[0108] In order to test the performance of the composite coating prepared by the present invention, the following characterizations were performed: Figure 1 This is the infrared spectrum of the NH2-POSS end-capped or suspended cross-linked fluorinated polyimide composite coating of comparative example 1. As can be seen from the figure, no characteristic absorption peaks of -COOH and -NH2 are found in the infrared curve, indicating that the imidization is complete.
[0109] Figure 2 The infrared spectrum of the 8NH2-POSS "star-shaped" cross-linked fluorinated polyimide composite coating of comparative example 2 is shown in the figure. -1 The COC absorption peak at 1083 cm -1 The absorption peak belongs to the Si-O-Si characteristic functional group, proving that POSS and fluorinated polyamic acid successfully underwent a “star-shaped” cross-linking reaction.
[0110] Figure 3 3 is the thermogravimetric curve of the coating of Example 3. It can be seen from the figure that the temperature at which the thermal weight loss is 5% is 536°C, indicating that the fluorinated polyimide-based composite coating has excellent heat resistance.
[0111] Figure 4 This is the corrosion performance test of the coating in Example 3, where the left figure is the Nyquist curve and the right figure is the Bode curve. It can be seen from the figure that the coating's |Z| 0.01 Hz The value is 1.01 × 10 11 Ω⋅cm 2 .
[0112] Figure 5 This is the corrosion performance test of the coating in Example 4, where the left figure is the Nyquist curve and the right figure is the Bode curve. It can be seen from the figure that the coating's |Z| 0.01 HzThe value is 1.12 × 10 11 Ω⋅cm 2 , has good barrier properties.
[0113] Figure 6 This is the corrosion performance test of the composite coating of Comparative Example 1, where the left figure is the Nyquist curve and the right figure is the Bode curve. It can be seen from the figure that the coating's |Z| 0.01 Hz The value is 1.26× 10 11 Ω⋅cm 2 .
[0114] Figure 7 This is the corrosion performance test of the composite coating of Comparative Example 2, where the left figure is the Nyquist curve and the right figure is the Bode curve. It can be seen from the figure that the coating's |Z| 0.01 Hz The value is 1.45 × 10 11 Ω⋅cm 2 .
[0115] Figure 8 The microscopic morphology and contact angle of the double-layer super-hydrophobic coating of Example 12, wherein (a) and (b) are the surface morphologies of the super-hydrophobic coating; (c) is the cross-sectional morphology of the composite coating; (d) is a diagram of the super-hydrophobic surface contact angle and the sliding contact angle. In Figure (d), CA is the static contact angle, and SA is the rolling contact angle. It can be seen from the figure that CA = 156.6° and SA = 5.6° of the super-hydrophobic coating, indicating that the super-hydrophobic coating has excellent hydrophobicity.
[0116] Fig. 9 The microscopic morphology and contact angle of the double-layer super-hydrophobic coating of Example 13, (a) is the surface morphology of the super-hydrophobic coating; (b) is the cross-sectional morphology of the composite coating; (c) is the super-hydrophobic surface contact angle and sliding contact angle diagram. In Figure (c), CA is the static contact angle and SA is the rolling contact angle. It can be seen from the figure that the CA of the super-hydrophobic coating is 161.6° and SA is 4.8°, indicating that the super-hydrophobic coating has excellent hydrophobicity.
[0117] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a super-hydrophobic polyimide-based anti-corrosion, anti-fouling and self-cleaning coating, characterized in that: The following steps are involved: S1: adding a modifying agent and graphene oxide to an organic solvent A, dispersing by ultrasonication, and then refluxing to obtain a modified GO; the modifying agent is at least one of POSS, a silane coupling agent, a chain alkylamine, and a chain alkyl isocyanate; S2: under nitrogen protection, adding dianhydride monomers in batches to a mixed solution of diamine monomers and organic solvent B, and after reaction, obtaining a polyamic acid solution, adding the polyamic acid solution to the modified GO, and ultrasonically dispersing to obtain a composite bottom layer slurry; coating the composite bottom layer slurry on the surface of the substrate, drying, and performing thermal imidization treatment to obtain a composite bottom layer; S3: coating the surface of the composite bottom layer with a composite top layer slurry comprising alkane siloxane or perfluorosiloxane-modified SiO2 and a binder, and after drying, obtaining the super hydrophobic polyimide-based anti-corrosion, anti-fouling and self-cleaning coating.
2. The method for preparing a super-hydrophobic polyimide-based anticorrosion and antifouling self-cleaning coating according to claim 1, characterized in that: In step S1, the polyamic acid is POSS cross-linked polyamic acid.
3. The method for preparing a super-hydrophobic polyimide-based anticorrosion and antifouling self-cleaning coating according to claim 1, characterized in that: In step S1, the POSS is one of monoamino oligomeric silsesquioxane, bisamino oligomeric silsesquioxane and octaamino oligomeric silsesquioxane.
4. The method for preparing a super-hydrophobic polyimide-based anti-corrosion and anti-fouling self-cleaning coating according to claim 1, characterized in that: In step S1, the number of carbon atoms in the chain alkyl group of the chain alkylamine and the chain alkyl isocyanate is 7-18.
5. The method for preparing a super-hydrophobic polyimide-based anti-corrosion and anti-fouling self-cleaning coating according to claim 1, characterized in that: In step S1, the graphene oxide accounts for 2.5% to 6.5% of the mass of the modification reagent.
6. The method for preparing a super-hydrophobic polyimide-based anti-corrosion and anti-fouling self-cleaning coating according to claim 1, characterized in that: In step S2, the dianhydride monomer is a fluorine-containing dianhydride monomer and / or the diamine monomer is a fluorine-containing diamine monomer.
7. The method for preparing a super-hydrophobic polyimide-based anti-corrosion and anti-fouling self-cleaning coating according to claim 1, characterized in that: In step S2, the modified GO accounts for 0.01% to 1.50% of the mass of the polyamic acid solution.
8. The method for preparing a super-hydrophobic polyimide-based anti-corrosion and anti-fouling self-cleaning coating according to claim 1, characterized in that: In step S3, in the composite top layer slurry comprising alkane siloxane or perfluorosiloxane modified SiO2 and a binder, the alkane siloxane or perfluorosiloxane modified SiO2 accounts for 0.01% to 1.50% of the mass of the binder.
9. The method for preparing a super-hydrophobic polyimide-based anti-corrosion and anti-fouling self-cleaning coating according to claim 1, characterized in that: In the step S3, before coating the composite top layer slurry, a PU intermediate layer is coated on the surface of the composite bottom layer, and then the composite top layer slurry is coated.
10. A super hydrophobic polyimide-based anticorrosion and antifouling self-cleaning coating, characterized in that: The composite coating is prepared by the method according to any one of claims 1 to 9; the impedance value of the composite coating is (1.32 to 3.29)×10 11 Ω⋅cm 2 The contact angle of the composite coating is 152°~159°, and the low-frequency impedance value is 7.04 × 10 10 Ω⋅cm 2 .
Citation Information
Patent Citations
Fluoropolymer anticorrosive coating for fastener and preparation method thereof
CN103342957A
Preparation method of graphene / polyimide composite adhesive
CN104164208A
Preparation method of grapheme-containing fluorinated polyimide composite corrosive-resisting coating
CN106349923A
Preparation method of graphene modified polyimide composite film
CN112795036A
Anti-corrosion and anti-icing self-cleaning super-hydrophobic coating as well as preparation method and application thereof
CN113372803A
Cited By
Fluorine-containing polyimide composite antifouling, anticorrosive and wear-resistant powder coating as well as preparation and application methods thereof
CN119978995A
Inorganic microcapsule-based hydrophobic anticorrosive filler as well as preparation method and application thereof
CN121895796A